Empowering public transport for urban environmental management - Abd Rahim Md Nor,; Nor Ghani Md Nor, (Environmental Management Society, Malaysia, 2006)
One of the key elements in urban environmental management is minimising dependence on the polluting petrol-propelled motorised vehicles. Use of low-occupancy vehicles such as personal cars and motorcycles is contrary to the aim of creating an environmentally sustainable eco-city because emissions from fuel-propelled vehicles are damaging the environment and health. This paper examines critically the current state of public transport service and efforts to empower its use as a way of minimising air pollution in Putrajaya, Malaysia’s newest federal government administrative city. Due to insufficient interest in public transport among the city dwellers, the city’s bus system was operating without profit and heavily dependent on the city authority to survive financially. The quality of the bus services was not very much dissimilar to those in other cities in the country in terms of availability, punctuality and reliability. The use of private cars and motorcycles is increasing rapidly and it is a matter of time before it will cause adverse impacts on the city’s environment. Signs of future environmental degradation in terms of reduced air quality, traffic noise, road accident, congestion and traffic chaos are already emerging. If the city authority failed to reverse this trend, Putrajaya would become just another city in the country where roads and highways are being dominated by private vehicles. To avoid this, and to revitalise public transport, the city has to adopt new approaches in the management of its bus system, and in determining the fares so that public transport will be more attractive